Vagabond princess : the great adventures of Gulbadan - Lal, Ruby (Yale University Press, 2024)
A captivating biography of one of the world's greatest adventurers, the itinerant Mughal Princess Gulbadan, based on her long-forgotten memoir "Finally, a serious consideration of Gulbadan's achievement.'"--Kirkus Reviews Situated in the early decades of the magnificent Mughal Empire, this first ever biography of Princess Gulbadan offers an enthralling portrait of a charismatic adventurer and unique pictures of the multicultural society in which she lived. Following a migratory childhood that spanned Kabul and north India, Gulbadan spent her middle years in a walled harem established by her nephew Akbar to showcase his authority as the Great Emperor. Gulbadan longed for the exuberant itinerant lifestyle she'd known. With Akbar's blessing, she led an unprecedented sailing and overland voyage and guided harem women on an extended pilgrimage in Arabia. Amid increasing political tensions, the women's "un-Islamic" behavior forced their return, lengthened by a dramatic shipwreck in the Red Sea. Gulbadan wrote a book upon her return, the only extant work of prose by a woman of the age. A portion of it is missing, either lost to history or redacted by officials who did not want the princess to have her say. Vagabond Princess contemplates the story of the missing pages and breathes new life into a daring historical figure. It offers a portal to a richly complex world, rife with movement and migration, where women's conviviality, adventure, and autonomies shine through.